Gis-based groundwater potential mapping in state of Melaka using analytical hierarchy process (AHP) technique / Irfan Aris - Aris, Irfan (2020)
The aim of this research is to use geographical information system (GIS) application with the aid of analytical hierarchy process (AHP) multi criteria decision analysis technique for groundwater potential mapping in the state of Melaka, Malaysia. As stated in this study, eight groundwater control parameters has been identified. The parameters are: lithology, slope, land use, soil, rainfall, drainage density, elevation, and geomorphology. Then the parameters were given judgment by Malaysia groundwater experts to derive its weightage and ranks. The weightage and ranks are derived using analytical hierarchy process (AHP) technique. The predicted groundwater potential map was classified into four distinct zones based on the classification scheme designed by Department of Minerals and Geoscience Malaysia (JMG). The results showed that about 7% of the study area falls under low potential zone, with 31% study area falls into moderate potential zone, 61% at high potential zone and only 1% falls very high potential zone. The results obtained in this study were validated with the groundwater borehole wells data compiled by the JMG and showed 31% of prediction accuracy. Results obtained from this study can be useful for future planning of groundwater exploration, planning and development by related agencies in Malaysia which provide a rapid method and reduce cost as well as less time consuming.